Psychophysiological Markers of Executive Functions during Copying Sentences - D.A. Momotenko; J.A. Gorbunov (Экспериментальная психология)
Typing is a multi-level process involving executive and motor functions. Due to its hierarchical organization, it becomes possible to study the psychophysiological features of higher mental functions in the natural environment by analyzing automated motor activity. The purpose of this work is to identify psychophysiological correlates of executive functions through computer typing. This study presents two EEG experiments aimed at copying sentences. The level of development of executive functions was measured using the UNIT and BRIEF-2 techniques, the sample consisted of 49 people (Age: M (SD) = 18.64 (0.74)), who previously confirmed the automation of the typing skill. According to the results of the study, regression models were constructed that reflect the dependence of the level of development of executive functions on alpha, beta and theta rhythms that arise during the printing of copied sentences. It was found that the higher the level of development of executive functions (braking, switching and working memory), the higher the power of beta rhythms in the prefrontal and frontal areas. Summarizing, we can talk about the significant contribution of executive functions to the typing processes, and about the possibilities of potential development of EF, by automating typing.